1966
DOI: 10.3181/00379727-121-30950
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Effect of Tylosin on a Mycoplasma Contaminant in A Tissue Culture Leukemia Cell Line.

Abstract: In view of the frequent contamination of tissue cultures with organisms of the pleuropneumonia group (PPLO), we are reporting the effectiveness of tylosin tartrate in elminating such a contaminant from our culture.During the attempt to plate in agar one of our lines of murine leukemia cells(l), we detected a filterable microorganism which may be related to Mycoplasma granu1arum.f Several chemotherapeutic and antibiotic agents, namely tetracyclin, kanamycin, erythromycin, chloromyce tin, polymixin, s tovarsol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1969
1969
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…However, it is well established that the presence of EBV-determined antigens is not necessary for the target cell to be lysed. On the chance that the isolation technique was inadequate, the cell line was treated with the antimycoplasma agent Tylocine accord-H. F. Pross and M. G. Baines: A Review of SLMC ing to Friend et al (1966). It is also possible, however, that in the process of in vitro transformation, the cells have become contaminated with mycoplasma, or a virus against which normal donors are reactive.…”
Section: Target Cell Characteristicsmentioning
confidence: 99%
“…However, it is well established that the presence of EBV-determined antigens is not necessary for the target cell to be lysed. On the chance that the isolation technique was inadequate, the cell line was treated with the antimycoplasma agent Tylocine accord-H. F. Pross and M. G. Baines: A Review of SLMC ing to Friend et al (1966). It is also possible, however, that in the process of in vitro transformation, the cells have become contaminated with mycoplasma, or a virus against which normal donors are reactive.…”
Section: Target Cell Characteristicsmentioning
confidence: 99%
“…The feasibility of extending this model to the quantitative assay of antibiotics is discussed. According to recent observations the inhibitory effect of antibiotics may be strongly affected by the milieu in which mycoplasmas are perhaps protected by their close association with cells (Gori & Lee, 1964;Friend, Patuleia & Nelson, 1966). That cell attachment involves an active biological process on behalf of either cell or mycoplasma has recently been reported by Fogh & Fogh (1967), who have also convincingly demonstrated that quantitative models of mycoplasma-cell interactions may lend themselves to more meaningful studies of effects of antibiotics.…”
Section: Introductionmentioning
confidence: 95%
“…MATERIALS AND METHODS Mycoplasma. The S-410 and S-743 strains were recovered from two murine leukemia tissue culture cell lines (5,6) by Charlotte Friend. The cell cultures were grown in basal media (Eagle) with Earle's balanced salt solution, supplemented with 15% fetal calf serum.…”
mentioning
confidence: 99%